Launch of the Nigeria Policies and Strategies (NPS) Seminar Series - Onilogbo, Omobolanle (CGIAR System Organization, 2022)
On 23 June 2022, the Nigeria Inception Workshop of the CGIAR National Policies and Strategies for Food, Land and Water Systems Transformation (NPS) Initiative1, took place in Abuja. The workshop, following the initiative’s global launch in May 2022 in Kenya, introduced NPS’ work in Nigeria, launched the Nigeria NPS Seminar Series, and featured presentations on the various CGIAR initiatives and stakeholder group discussions. Several participants representing the Government of Nigeria, civil society actors, researchers, and development practitioners were in attendance. Participants and stakeholders from Nigeria, along with the NPS initiative team and other CGIAR initiatives, were brought together at the inception event to brainstorm strategies to achieve the priority areas of the NPS initiative, including Building policy coherence and integrating policy tools and Responding to crises.